SHOULD INDONESIAN FISHERY POLICIES BE NAVIGATED TOWARDS THE INHERENT WEALTH OF FISHERIES OR SMALL-SCALE FISHERMEN’S WELFARE? - R.A. Nidha Nadia (OISAA, 2018)
The marine fishery policies have been challenged by splitting objectives in the fishery managementdirected towards the inherent wealth of fisheries or the small-scale fishermen’s welfare. This research thusinvestigated the marine fishery policies in Indonesia, with a particular observation on the small-scalefishermen’s livelihood on the north coast of Jakarta. The objectives of the study include comprehendingand analysing the rationale, potential, challenges, and the impact of the Indonesian fishery policies in termsof the multidimensional global challenges of sustainability, and that of contextual challenges offishermen’s livelihood. This research primarily utilised a case study on north coast of Jakarta and secondaryresource in the form of literatures on Indonesian fishery policies. The data collected are constructed usingthe approach of fishery management objectives towards wealth or welfare orientation. The result indicatesthat in spite of the tendency of divided fishery management approach to wealth or welfare, the globalfishery policies and Indonesian fishery policies in particular cannot distinctly separate the two objectives,which results in multidimensional fishery policies with interwoven targets. Task delegation from thecentral government to the regional government for small-scale fishermen’s livelihood affairs is thenimplemented; meanwhile the central government pursues a bigger ambition towards sustainable,prosperous, and sovereign fishery. Additionally, the research argues that small-scale fishermen’sincreasing consciousness towards the importance of the sustainability of fishing has shed some light on thecooperation between the government and the small-scale fishermen in programmes that can both improvesmall-scale fishermen’s livelihood and generate the inherent wealth of fisheries.